Conductivity and morphological characteristics of untreated and alkali treated natural fibre reinforced lldpe-nr polymer composite - Sunthrasakaran, Nishanthi (2022)
Polymer nanocomposite has been actively explored in dielectric insulation studies due to its exceptional electrical properties exhibited by these materials. However, inferior properties of polymer biocomposite which is the hydrophilic properties causes less attention in dielectric insulation field. Besides that, the natural fibre waste could be used for a good cause that contributes to Sustainable Development Goals (SDG). Hence, this research is aimed to study the polarization current, depolarization current and conductivity of linear-low density polyethylene (LLDPE-NR) with three different types of natural fibre as filler which are empty fruit bunch (EFB), oil palm frond (OPF) and pineapple leaf fibre (PALF). The samples were fabricated with LLDPE-NR (80:20) as the matrix and compatibilizer by varying the percentage of EFB, OPF and PALF fibre (2.5%, 5%, 7.5% and 10%). The fibres were pre-treated for 6 hours with 5% of sodium hydroxide solution (NaOH) under room temperature. The sample were then fabricated with treated and untreated fibres to assess the difference thoroughly. Moisture absorption test (ASTM D570) was presented for degradation effect. Morphological tests (FESEM, EDX and FTIR) were conducted to monitor the effect of alkali treatment on the fibres and the physical structure of the polymer biocomposite. Result obtained indicates that samples that consist of alkali treated EFB, OPF and PALF exhibits lesser agglomeration compared to sample with untreated fibres which indicates better adhesive properties. The conductivity of each sample was measured using Polarization and Depolarization Current (PDC) testing values. Result indicated 10% of treated OPF fibre is the optimum filler concentration with lowest maximum conductivity value 48.76pS/m under normal condition. Whereas, 2.4% of treated EFB fibre exhibits lowest maximum conductivity with 84.7pS/m under wet condition. In general, treated OPF and EFB fibre performs better when incorporated with LLDPE-NR by exhibiting lower electrical conductivity compared to PALF fibre